2004
DOI: 10.1161/01.hyp.0000112304.26158.5c
|View full text |Cite
|
Sign up to set email alerts
|

Tempol Lowers Blood Pressure and Sympathetic Nerve Activity But Not Vascular O 2 in DOCA-Salt Rats

Abstract: This study tested the hypothesis that depressor responses caused by tempol are not associated with reductions in vascular O2- levels in urethane-anesthetized deoxycorticosterone acetate (DOCA)-salt hypertensive rats. We compared the effects of intravenous (IV) administration of tempol, apocynin, superoxide dismutase-polyethylene glycol (PEG-SOD), and SOD on mean arterial blood pressure (MAP), heart rate (HR), and renal sympathetic nerve activity (RSNA). In DOCA-salt rats, tempol (30 to 300 micromol/kg) dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 45 publications
7
94
0
1
Order By: Relevance
“…In addition, our in vitro studies showed that a similar concentration of SNP was required to inhibit NKA activity in lean and obese proximal tubules. Although the scavenging of superoxide radicals remains the central mechanism for its blood pressure-lowering mechanism, the effect of tempol on direct sympathetic nerve activity inhibition and heme-oxygenase system is also well documented (34,35). Recently, Yang et al (35) reported that tempol inhibits O 2 Ϫ -induced degradation of hypoxia-inducible factor-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our in vitro studies showed that a similar concentration of SNP was required to inhibit NKA activity in lean and obese proximal tubules. Although the scavenging of superoxide radicals remains the central mechanism for its blood pressure-lowering mechanism, the effect of tempol on direct sympathetic nerve activity inhibition and heme-oxygenase system is also well documented (34,35). Recently, Yang et al (35) reported that tempol inhibits O 2 Ϫ -induced degradation of hypoxia-inducible factor-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, Nakazono et al 24 showed that HB-SOD, which is a fusion protein consisting of human Cu/Zn-type SOD and a C-terminal basic peptide with high affinity for heparan sulfate on endothelial cells, significantly decreased blood pressure in SHR. From these observations, it seems likely that membrane permeability, a half-life, and/or distribution of these drugs or tempol might be critical for their effects on blood pressure and RSNA.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Acute tempol treatment of normotensive, DOCA-salt and spontaneously hypertensive rats (SHRs) inhibits sympathetic nerve activity and this effect is not prevented by nitric oxide synthase (NOS) inhibition. [2][3][4][5][6] Local application of tempol onto renal sympathetic nerves decreased nerve activity without changing blood pressure (BP) or heart rate (HR). 7 The results suggested that changes in K ϩ channel activity might contribute to sympatho-inhibition caused by tempol.…”
Section: S Uperoxide Anion (Omentioning
confidence: 99%
“…Sham operated and DOCA-salt hypertensive rats (male, 170 to 225 grams; Charles River Laboratories) were prepared as previously de-scribed. 2,6 Blood pressure was measured in conscious animals by tail-cuff plethysmography 4 weeks after DOCA implantation.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation